Evaluation of Biomedical Ti/ZrO2 Joint Brazed with Pure Au Filler: Microstructure and Mechanical Properties - Yuzhen Lei; Hong Bian; Wei Fu; Xiaoguo Song; Jicai Feng; Weimin Long; Hongwei Niu (Metals, 2020)
Titanium and zirconia (ZrO2) ceramics are widely used in biomedical fields. This study aims to achieve reliable brazed joints of titanium/ZrO2 using biocompatible Au filler for implantable medical products. The effects of brazing temperature and holding time on the interfacial microstructures and mechanical properties of titanium/Au/ZrO2 joints were fully investigated by scanning electron microscopy (SEM), energy-dispersive spectrometry (EDS) and X-ray diffraction (XRD). The results indicated that the typical interfacial microstructure of the titanium/Au/ZrO2 joint was titanium/Ti3Au layer/TiAu layer/TiAu2 layer/TiAu4 layer/TiO layer/ZrO2 ceramic. With an increasing brazing temperature or holding time, the thickness of the Ti3Au + TiAu + TiAu2 layer increased gradually. The growth of the TiO layer was observed, which promoted metallurgical bonding between the filler metal and ZrO2 ceramic. The optimal shear strength of ~35.0 MPa was obtained at 1150 °C for 10 min. SEM characterization revealed that cracks initiated and propagated along the interface of TiAu2 and TiAu4 reaction layers.